Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Siswa Sekolah Dasar: Implementation of the Snowball Throwing Type Cooperative Learning Model to Improve Elementary School Students' English Vocabulary Mastery - Afifatur Rohmah Wafiyah; Miftahul Jannah (ITScience (Information Technology and Science), 2026)
Vocabulary mastery is a fundamental aspect of learning English in elementary school because it lays the foundation for other language skills. However, conventional learning often makes students less active, leading to limited vocabulary mastery. Therefore, a more interactive and enjoyable learning strategy is needed. This study aims to analyze the effect of implementing the Snowball Throwing cooperative learning model on third-grade students' English vocabulary mastery at SD N 1 Pandansari. This study used a quasi-experimental design with a Randomized Pretest–Posttest Control Group Design approach. The research subjects were 54 students, divided into two groups: the experimental group and the control group, each consisting of 27 students. Data were collected through English vocabulary tests and psychomotor assessments. Data analysis was carried out using nonparametric statistics: the Mann-Whitney U Test to compare the two groups and the Wilcoxon Signed-Rank test to assess differences before and after treatment. The results showed a significant increase in students' vocabulary mastery in the experimental group (p = 0.000; <0.05). In the psychomotor aspect, a difference was also found between the pretest and posttest with a p-value of 0.016 (<0.05). This finding indicates that implementing the Snowball Throwing cooperative learning model effectively improves elementary school students' English vocabulary mastery. Therefore, this method can be an alternative learning strategy that can improve student engagement and learning outcomes.